The challenge of sustainable development: From technocracy to democracy-oriented political economics - Peter Söderbaum (Economic Thought, 2021)
Mainstream neoclassical economics, as well as heterodox schools, should be regarded as different kinds of 'political economics'. There is no value-free economics. We therefore need to bring democracy into economics. The present challenge of sustainable development suggests that a new conceptual framework in economics is needed. In this essay, a political and democratic view of individuals, organisations, decision-making, markets, assessment of investment projects and policy options is proposed. The imperative of democracy also implies that the close-to-monopoly position of neoclassical theory and method at university departments of economics has to be replaced by pluralism. There is a continued role for neoclassical theory and method, considering the fact that millions of professionals globally have been indoctrinated in this particular way of understanding efficiency and governance, but the idea that neoclassical theory is best for all purposes has to be abandoned.
Keywords: 330; sustainable development; democracy; political economics; political economic person; ideological orientation; political economic organisation; mission; decision-making; matching; positional analysis; actor-network perspective